2022
DOI: 10.1038/s41396-022-01259-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyanophages from a less virulent clade dominate over their sister clade in global oceans

Abstract: Environmental virus communities are highly diverse. However, the infection physiology underlying the evolution of diverse phage lineages and their ecological consequences are largely unknown. T7-like cyanophages are abundant in nature and infect the marine unicellular cyanobacteria, Synechococcus and Prochlorococcus, important primary producers in the oceans. Viruses belonging to this genus are divided into two distinct phylogenetic clades: clade A and clade B. These viruses have narrow host-ranges with clade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…To compare the infection kinetics of cyanopodoviruses under identical conditions, we used Prochlorococcus MED4 as the host, which can be infected by both the MPP-C and MPP-B phages. Two MPP-B phages P-SSP7 and P-GSP1 showed similar one step infection dynamics with latent periods of 6–8 h, which are consistent with previous studies of these two phages [ 51 , 62 , 63 ]. Following the latent period, the amounts of extracellular phage DNA for P-SSP7 and P-GSP1 increased exponentially until the plateaus were reached at ~16 hours after infection (Fig.…”
Section: Resultssupporting
confidence: 90%
“…To compare the infection kinetics of cyanopodoviruses under identical conditions, we used Prochlorococcus MED4 as the host, which can be infected by both the MPP-C and MPP-B phages. Two MPP-B phages P-SSP7 and P-GSP1 showed similar one step infection dynamics with latent periods of 6–8 h, which are consistent with previous studies of these two phages [ 51 , 62 , 63 ]. Following the latent period, the amounts of extracellular phage DNA for P-SSP7 and P-GSP1 increased exponentially until the plateaus were reached at ~16 hours after infection (Fig.…”
Section: Resultssupporting
confidence: 90%
“…There are few studies of decay rates among marine phage isolates [ 67 ]. However, a recent study found that strains within two major lineages of cyanopodoviruses (clade A and B) did not differ significantly in their decay rates, despite these clades having clear differences in host range and lifestyle strategies [ 70 ]. Because phage decay is an important factor in the dynamics of community composition, more analysis of decay rate variation within a phylogenetic framework, especially for cyanomyoviruses, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Using the polony method, we quantified TIM5-like cyanophages over the annual cycle in the Red Sea at 20 m depth in 4 years between 2013 and 2016 (Figure 3). During this period, the water column exhibited typical seasonal dynamics for the Red Sea (Carlson et al, 2014;Lindell & Post, 1995;Maidanik et al, 2022). In the winter, the upper layers of the water column were colder (Figure 3A), which drove deep convective mixing and the influx of nutrients into the photic zone that stimulated phytoplankton productivity observed in increased chlorophyll concentrations (Figure 3B).…”
Section: Seasonal Distribution Patterns Of Tim5-like Cyanophages In T...mentioning
confidence: 97%
“…As the water column warmed from spring to early autumn (Figure 3A), the water column stratified. This is generally associated with succession of the phototrophic community from picoeukaryotes in winter, Synechococcus in early spring and Prochlorococcus in summer (Lindell & Post, 1995;Maidanik et al, 2022) and is reflected in the decreasing chlorophyll-a concentrations (Figure 3B). Maximum Synechococcus abundances, observed with monthly resolution, occurred in March following the onset of stratification after convective mixing.…”
Section: Seasonal Distribution Patterns Of Tim5-like Cyanophages In T...mentioning
confidence: 97%
See 1 more Smart Citation